A Review of Insights into Algae as a Sustainable Bio-based Photocatalyst for Environmental Remediation - Ramadhani Ramadhani; Ahmad Said (CV FOUNDAE, 2024)
Algae have recently emerged as a promising photocatalyst material due to their abundancy, low cost, and environmentally friendly nature. This review summarizes recent progress on utilizing algae as bio-based photocatalysts. Eutrophication and abundance of algae which make it an ideal candidate as a sustainable photocatalyst source, have been discussed. Recent work on synthesis methods such as hydrothermal treatment, calcination, and templating to produce photocatalytically active algae nanoparticles (NPs) has been reviewed. Photocatalytic activity of algae-based materials have been studied such as wastewater treatment, dye removal, and heavy metal remediation. Finally, strategies to further enhance algae's photocatalytic performance, including coating and doping with metals, coupling with graphene, and heterogeneous integration are highlighted here. To wrap up, this review underscores the exciting potential of algae as a sustainable and effective next-generation photocatalytic material.